Resolution No. 507/2024 of the Brazilian National Environmental Council: the discourses present in its drafting process - Lucena, Marcelo Silva de; Zakia, Maria José Brito (Sustainability in Debate, 2025)
Given that conceptions about sustainable forest management (SFM) are shaped by discourses that propose different "world views", we characterise, based on discourse theory, the discourses and narratives present in the drafting process of Resolution No. 507/2024 of the Brazilian National Environmental Council, aimed at regulating the SFM of the Caatinga. The production of the Resolution was marked by discourses and coalitions that propose alternative and, to some extent, contrasting narratives about institutional action related to forest governance and SFM, as well as to the sustainable exploitation of forest resources. The dominance of the administrative simplification discourse reflects an imbalance of power and the consolidation of a “technical-bureaucratic” approach to forest management and SFM. However, it was widely understood that SFM could enable the transition beyond forest extractivism, establishing itself as a forestry policy essential for ensuring the sustainability of the Caatinga.